CITY INFORMATION AND COMMUNICATION NETWORKS AS MEANS OF INCRISING PARTICIPATION: CASE STUDY OF MUNICIPALITY OF INĐIJA, SERBIA - Brković, Matija; Sretović Brković, Višnja (Arhitektura i urbanizam, 2014)
City information and communication networks are specific form of local online communities, designed for inhabitants of particular city, its administration, municipality service providers, investors, tourists, as well as any others interested party. This paper studies the potential of such networks to assist public participation in city planning and management. It explores the benefits and potential pitfalls of using such technologies. In addition, the paper will present and analyze the city information and communication network created and used by the municipality of Inđija. In 2002, the municipality made a strategic development plan, in which the improvement of local administration was among the first priorities. The administration started the installation of an integrated information system right away – essentially creating e-government platform – in order to enable all citizens to participate in solving local problems, as well as to facilitate their day-to-day communication with the local administration.
Keywords: city information and communication network; Internet; Inđija; Serbia; urban planning; participation